Bioaccesibilidad de proteínas - García Pinedo, Gustavo Andree (2022)
Nowadays, people are more concerned about their health, and the trend for the consumption of healthy foods is increasing. There are different nutritional claims about various foods, however, just knowing the nutritional content is not enough, since the use and benefits that these can have in the body are little known, since it depends on different variables. Likewise, the importance of proteins in the diet is known, however terms such as protein quality and the biological value of proteins have drawn attention, since the fact that a certain food has a high protein content does not mean that the body is able to use it fully. Given this, as much as bioaccessibility and bioavailability have taken center stage for the determination of these parameters, the first allows us to know the fraction released from the bioactive component of the food matrix and the second is the fraction of the nutrient that the body can use in its metabolic functions. Knowing the bioaccessibility of a certain nutrient is extremely important, since it is also influenced by other food compounds that could chelate the bioactive compound, preventing its correct release from the matrix. To determine the bioaccessibility of active compounds, various in vitro techniques have been developed, which aim to mimic or imitate gastrointestinal conditions in terms of pH, enzymes and movement. However, these methods are more useful for the analysis of the end points of the digests, but they do not allow us to analyze the kinetics of digestion since they are more complex processes, which cannot be determined in vitro. And taking into account that foods rich in protein, such as meat and dairy products, are consumed daily by millions of people in the world, more research is needed that allows us to provide information on the behavior of their proteins after being ingested.